Energy potential from Areca Palm through Direct Combustion and Pyrolysis in Indonesia: A review - Setyawan, Hendrix Yulis; Sunaryo, Sunaryo; Waluyo, Budi; Merlya, Merlya; Choirun, Annisa'u; Nizori, Addion; Sahrial, Sahrial (Department of Technology of Agricultural product (THP) Jambi University, 2020)
Global warming that occurs due to rapid population growth and increasing of energy consumption makes energy supply decreases. Energy source from non-renewable energy (fossil fuel) cause increasing greenhouse gas emission level and scarcity of natural resources. This paper reports that agricultural residues especially areca palm wastes had been widely used as an alternative energy source to reducing fossil fuel consumption. About 4.780.000 tones areca palm produced per year around the world and the shell was burned in open air or just thrown in the environment. This work aimed to investigate energy potential from areca palm shell using direct combustion and pyrolysis method also do analysis about this technology from environmental point of view and that contribution for sustainable uses.